Impact of MET inhibitors on survival among patients with non-small cell lung cancer harboring MET exon 14 mutations: a retrospective analysis. (July 2019) - Awad, Mark M.; Leonardi, Giulia C.; Kravets, Sasha; Dahlberg, Suzanne E.; Drilon, Alexander; Noonan, Sinead A.; Camidge, D. Ross; Ou, Sai-Hong I.; Costa, Daniel B.; Gadgeel, Shirish M.; Steuer, Conor E.; Forde, Patrick M.; et al.
Highlights: The impact of MET inhibition on survival in MET exon 14 mutant NSCLC is unclear. Use of a MET inhibitor in MET ex14 NSCLC is associated with improved survival. The median progression-free survival to crizotinib in MET ex14 NSCLC was 7.4 months. Abstract: Objectives: Although dramatic responses to MET inhibitors have been reported in patients with MET exon 14 ( MET ex14) mutant non-small cell lung cancer (NSCLC), the impact of these treatments on overall survival in this population is unknown. Methods: We conducted a multicenter retrospective analysis of patients with MET ex14 NSCLC to determine if treatment with MET inhibitors impacts median overall survival (mOS). Event-time distributions were estimated using the Kaplan-Meier method and compared with the log-rank test. Multivariable Cox models were fitted to estimate hazard ratios. Results: We identified 148 patients with MET ex14 NSCLC; the median age was 72; 57% were women and 39% were never smokers. Of the 34 metastatic patients who never received a MET inhibitor, the mOS was 8.1 months; those in this group with concurrent MET amplification had a trend toward worse survival compared to cancers without MET amplification (5.2 months vs 10.5 months, P = 0.06). Of the 27 metastatic patients who received at least one MET inhibitor the mOS was 24.6 months. A model adjusting for receipt of a MET inhibitor as first- or second-line therapy as a time-dependent covariate demonstrated that treatment with a MET inhibitor was associated with a significant prolongation in survival (HR 0.11, 95% CI 0.01-0.92, P = 0.04) compared to patients who did not receive any MET inhibitor. Among 22 patients treated with crizotinib, the median progression-free survival was 7.4 months. Discussion: For patients with MET ex14 NSCLC, treatment with a MET inhibitor is associated with an improvement in overall survival.